KGID : Konstant Grcic industrial design. - Böhm, Florian, 1969- (London : Phaidon, 2007)
German designer Konstantin Grcic was born in Munich in 1965. After opening his practice KGID (Konstantin Grcic Industrial Design) in 1990, he very quickly received recognition for his simple, ingenious products. With numerous commissions from the most important names in the design industry, such as Authentics, Flos, iittala, Krups, Magis and Muji, his work has been widely published in several books and design reviews, and has been awarded the prestigious Compasso d'Oro (Milan, 2001) and Nombre d'Or (Paris, 2004), among others. Grcic describes himself as a mix of German mentality and English education. Following his initial training as a cabinetmaker, from which he retains the hands-on approach and sensitivity to materials of a craftsman, Grcic went on to study contemporary design at the Royal College of Art in London. This formative experience added a new dimension to his fascination with making things. As a result, every one of his products is characterized by his careful research into
The history of design and architecture, and his passion for technology and materials. So much so, that Achille Castiglioni, one of the most significant Italian designers of the twentieth century, considered him to be his 'spiritual heir'. Blending restraint of form and materials with a sense of playfulness, his products have an immediate universal appeal. They are simple and minimalist, but Grcic always gives a new take to straightforward and common objects. This can be clearly seen in his acclaimed Mayday lamp (2001), which instantaneously became a design icon and was selected for the permanent collection of the Museum of Modern Art, and in his most recent project, the die-cast aluminium chair_ONE (2004), in which he experimented with a technology rarely used in large-scale objects. The book presents the work of KGID, showcasing a remarkable portfolio of products and design concepts with especially commissioned photographs and original drawings. It also offers a rare insight into his design
Process by showing the various stages of a product's development through sketches, models, computer renderings and snapshots at the workshops of KGID and several manufacturers. With texts by Konstantin Grcic, Pierre Doze and Francesca Picchi, and conceived by Florian Bohm and Konstantin Grcic, this is the first publication on one of the most interesting and prolific designers of today.